(Un-)Stable Preferences, Beliefs, and the Predictability of Behaviour - Irenaeus Wolff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
I show that whether participants generally believe in others' preference stability is a crucial determinant of behaviour. Whether a participant's behaviour can be predicted by her best-response or a Nash-equilibrium in a context where she can observe others' elicited preferences depends heavily both on the participant having stable preferences and on her generally believing in others' preference stability. The latter is true because such a belief is associated with less dispersed beliefs.
Keywords: C72; 330